A. Bernard Knapp and Stella Demesticha. Mediterranean connections: maritime transport containers and seaborne trade in the Bronze and Early Iron Ages. - Dickinson, Oliver (Journal of Greek Archaeology, 2019)
This is a fairly short but important book that focuses on the part played in seaborne trade by the ‘maritime transport containers’ of the title (hereafter MTCs). It is packed with data; it is particularly useful to have authoritative accounts of the east Mediterranean material and of the great quantities of information now available from provenance studies and organic residue analysis. Almost inevitably some more recent studies like Stockhammer 2015 (which must have come out as it went to press) have been missed, but in general the coverage of the mass of accounts and studies of the material seems close to comprehensive.